Много нас было: записки пулеметчика / Петр Любомиров - Любомиров Петр Петрович (Удмуртия, 1988)
Экземпляры: 1 (20160414) / Инвентарный номер: 16435 / Цена: 0.90 / Сис.шифр: С(Удм) / Авт.знак: Л 93 / ГРНТИ: 17.82 / ББК: С(Удм)